Analysis of Factors Affecting Profitability of Islamic Banks in Yogyakarta - Aini, Ratri Zhohratun; Rusdianto, Rusdianto (Islamic Economics Journal, 2024)
Islamic banks have a strategic task to encourage economic growth and national progress. The greater the contribution of banking, it is estimated that the more advanced a country’s economy will be. As a financial institution, Islamic banks must also pay attention to their performance to operate well and develop rapidly in Indonesia, one of which is by paying attention to financial performance through financial reports. Profitability is an assessment aspect used to measure bank performance in generating profits. This study aims to determine the results of the effect of mudharabah and musyarakah financing on bank profitability as measured using ROA by comparing the company's net income with the total assets it has as a whole. The data analysis method uses secondary data obtained from the monthly financial statement data of Islamic Banks on mudharabah financing and musyarakah financing with the help of SPSS 27 software. The results showed that mudharabah and musyarakah financing had a positive and significant effect on the profitability of Islamic Banks in 2018-2022. This shows that the increasing value of the contract distributed also contributes to increased profitability. It is hoped that a significant increase in profitability can attract investors to invest more in Islamic Banks.